Indigo derivatives-incorporated functional polyhydroxybutyrate polymer with controlled biodegradability - Park, Seo A.; Choi, Kwon Young (Dyes and Pigments, 2022)
Indigo derivatives incorporating Poly(3-hydroxybutyrate) (IDPs) were produced in a single recombinant Escherichia coli strain by a one-pot process. The E. coli cells expressed enzymes involved in two different synthesis pathways: genes for Poly(3-hydroxybutyrate) (PHB) synthesis (phaB, phaC, and bktb), and the gene for synthesizing indigo derivatives (CYP102G4). PHB is a well-known biodegradable polymer, the monomers of which are synthesized and polymerized in a single host cell, while indigo is a well-known indole-derived colorant that has been used for denim dyeing. Depending on the indole derivatives used in the feed, indigo derivatives with different colors were synthesized through the action of the CYP102G4 enzyme. The indole derivatives included 5-Cl, 6-Cl, 7-Cl, 5-Br, 5-OH, 5-OCH3, 4-NO2, and 5-NO2 indole. Engineered Escherichia coli cells fed with each indole derivative simultaneously generated IDPs. Several biological and physical properties, such as the antioxidant activity, biodegradability, melting temperature (Tm), glass transition temperature (Tg), average molecular weight, polydispersity index, hardness, and elasticity of the IDPs were analyzed. Among the IDPs, 5-OH IDP showed a higher Tm of 181.1 °C and thermostability, whereas 4-NO2 IDP showed the lowest Tm of 154.7 °C. And the biodegradability varied depending on the incorporated indigo derivatives. 5-OH IDP was the most resistant to biodegradation, with the lowest weight loss of 2.6%, while 4-NO2 IDP showed the highest weight loss of 18.9%. Moreover, significant changes in the hardness, analyzed by nanoindentation, were observed with 4-NO2 incorporated IDP. Finally, the produced IDPs were used as a cellulose coating, which resulted in differently packed surface structures without loss of coloration. The results of this study can be further extended to developing functional biodegradable polymers with characteristic coloration.
Keywords: Cellulose dyeing; Indigo derivatives; Indole derivatives; PHB; Poly(3-hydroxybutyrate); Poly--3-hydroxybutyrate; Poly-3-hydroxybutyrate; Polyhydroxybutyrate; Synthesised; Weight loss; Biodegradability; Cellulose dyeing; Indigo derivatives; PHB; Polyhydroxybutyrate